Conceptualization of spiritual intelligence quotient (SQ) in the Islamic Fintech adoption - Norafni @ Farlina Rahim,; Mohammed Hariri Bakri,; Siti Norbaya Yahaya, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Fintech or financial technologies is currently a new phenomena in the banking and financial industry. Islamic Finance industry also embracing this new technology and sweeping across the financial world to be part of the revolution. The studies of Islamic Fintech is still limited and underexplored, particularly on the demand side i.e.consumer. This paper intended to examine the influence of spiritual intelligence quotient (SQ) to the behavioral intention of Islamic Fintech adoption among consumers in Malaysia. To achieve this objective, this paper adopts a content analysis approach. The analysis is drawn from the perusals of academic journals and relevant documents based on thematical theories in SQ and adoption of Islamic Fintech. The review has found that SQ have positive nexus with behavior of consumers in Islamic Fintech adoption.